Employees’ organizational citizenship behaviour toward the environment : a conditional mediation model - Ju, Soon Yew, @ Yew, Soon Yu (2019)
An emergent body of knowledge has acknowledged that organizational environmental management practices are associated with employees’ organizational citizenship behaviour toward the environment. Nonetheless, barely is known about the moderating and mediating mechanisms that triggering this relationship. Based on social exchange theory and an affect theory of social exchange, the study explored whether affective commitment towards environment function as an indirect effect of the relationship between organizational environmental management practices and employees’ organizational citizenship behaviour toward the environment, and further explore whether this indirect effect is moderated by environmental leadership. This research model was examined using information gathered from 244 local authority's employees from Peninsular Malaysia. Respondents accomplished questionnaires measuring their perceptions of organizational environmental management practices, affective commitment towards environment, environmental leadership, and employees’ organizational citizenship behaviour toward the environment. After controlling for demographic variables (gender, age, and tenure) and social desirability bias, organizational environmental management practices was positively correlated with employees’ organizational citizenship behaviour toward the environment. Indirect effect analysis revealed that affective commitment towards environment mediated the relationship between organizational environmental management practices and employees’ organizational citizenship behaviour toward the environment. The Johnson-Neyman regions of significance technique indicated that the relationship between organizational environmental management practices and affective commitment towards environment was significant when environmental leadership was above 0.578 plus one standard deviation from mean and below -1.253 minus one standard from mean. Tests of conditional indirect effect extended that the indirect effect path was stronger for employees with high environmental leadership group. Results of this study underline the importance of pinpointing the mechanisms that moderate the indirect effect paths between organizational environmental management practices and employees’ organizational citizenship behaviour toward the environment.